Vulnerability To Health in A Ward of Bengaluru: Insights from A Mobile-Based Survey - Ravish KS; Ashwini Lonimath; Vani HC; I Sushil Kumar; Ranganath TS (Medsci Publications, 2022)
Context/Background: Rapid urbanization has resulted in a growing number of people living in under-served areas with inadequate and overburdened infrastructure and services, worsening of environmental factors. Sustainable Development Goal 11: "sustainable cities and communities", highlights, there is an ur-gent need to re-orient the community development strategies by adopting economically & technologically sustainable models. Aims/Objectives: An application-based household survey to assess the vulnerability and Health condi-tions among the urban poor of slums in Bengaluru. Methodology: The tool for Vulnerability Assessment by Government of India was modified to develop a user-friendly tool for Community Health Workers in an Android-based smartphone application (Namma Samudaya). Data was collected through house-to-house survey. Results: A total of 3165 households (HHs) were surveyed. Among these, 54.2% of the HHs belong to vul-nerable category and 45.8% to highly vulnerable group. Conclusions: Domain-wise analysis showed, Residential -25.2% of HHs were located besides polluted wa-ter Social - "No social support" and "disability" was reported by 3% of households each; Health-Related - Catastrophic Health expenditure in the past 1 year was reported by 40.4% HHs. The baseline information of slums & their geographic mapping obtained during the survey can be used as foundation for effective plan-ning of health care services.